2020
DOI: 10.1002/mds.28224
|View full text |Cite
|
Sign up to set email alerts
|

Increased Blood Pressure Dipping in Restless Legs Syndrome With Rotigotine: A Randomized Trial

Abstract: The objective of this study was to assess the rotigotine effect on the nocturnal blood pressure (BP) dip by 24-hour ambulatory BP monitoring and on endothelial function in patients with restless legs syndrome (RLS) compared with placebo. Methods: In this double-blind, placebo-controlled trial, 76 adult patients with moderate to severe RLS and periodic legs movements in sleep index ≥10/hour were randomized to rotigotine at optimal dose of 3 mg per day or placebo for 6 weeks. A total of 6 patients had a major pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Several studies have demonstrated an association between RLS and frontal-executive dysfunction, reduced cognitive flexibility, and reduced attention, while others have shown no association between RLS and cognition (Gao et al, 2021). However, a metanalysis demonstrated a negative association between RLS severity and global cognitive function, as measured by the Minimental status exam or MoCA (Chenini et al, 2020), and in another study of patients with an average age of 56, attention was agitated, as measured by the Stroop test or Trails making B test (Jung, 2015). Furthermore, a recent retrospective cohort study of over 2,500 people over 60 years old with up to 12 years of follow-up showed a 1.74 times increased risk of all-cause dementia in people with RLS and a higher risk of developing vascular dementia over Alzheimer's dementia (Xu et al, 2022).…”
Section: General Considerationsmentioning
confidence: 99%
“…Several studies have demonstrated an association between RLS and frontal-executive dysfunction, reduced cognitive flexibility, and reduced attention, while others have shown no association between RLS and cognition (Gao et al, 2021). However, a metanalysis demonstrated a negative association between RLS severity and global cognitive function, as measured by the Minimental status exam or MoCA (Chenini et al, 2020), and in another study of patients with an average age of 56, attention was agitated, as measured by the Stroop test or Trails making B test (Jung, 2015). Furthermore, a recent retrospective cohort study of over 2,500 people over 60 years old with up to 12 years of follow-up showed a 1.74 times increased risk of all-cause dementia in people with RLS and a higher risk of developing vascular dementia over Alzheimer's dementia (Xu et al, 2022).…”
Section: General Considerationsmentioning
confidence: 99%
“…Rotigotine (Neupro) patches can provide patients with round-the-clock symptom control because of their continuous, progressive, all-day release. [ 65 ] This extended duration of action and sustained release of dopamine into the blood may minimize dopamine fluctuations at the receptor and may be associated with a low propensity to evolve into potentiation syndrome. [ 65 ] The dose of rotigotine can be started at a patch strength of 1.0 mg and increased weekly to a maximum daily dose of 2.0 or 3.0 mg. [ 66 ] Clinical trials of rotigotine have shown that a further dose increase to 4.0 mg per day could be considered, but this high dose may carry a greater risk of enhancement.…”
Section: Therapeuticsmentioning
confidence: 99%
“…[ 65 ] This extended duration of action and sustained release of dopamine into the blood may minimize dopamine fluctuations at the receptor and may be associated with a low propensity to evolve into potentiation syndrome. [ 65 ] The dose of rotigotine can be started at a patch strength of 1.0 mg and increased weekly to a maximum daily dose of 2.0 or 3.0 mg. [ 66 ] Clinical trials of rotigotine have shown that a further dose increase to 4.0 mg per day could be considered, but this high dose may carry a greater risk of enhancement. [ 67 ] Rotigotine, as a transdermal patch, may cause skin reactions, such as excessive itching or redness of the skin at the application site.…”
Section: Therapeuticsmentioning
confidence: 99%